Use of steel-reinforced concrete for internally heated structures - Cross, Alan (Knovel, 2010)
"The need to reduce the cost of the enclosure material for direct fired heaters or power boilers prompted this study, whose purpose was to determine whether significant cost savings could be achieved if the structural enclosures of such heaters employed steel-reinforced concrete construction rather than steel plate and structural steel construction."--Description from Knovel website.